Strategi Pembelajaran Pendidikan Agama Islam pada Peserta Didik Berkebutuhan Khusus - Amalia, Sarah; Wahyudi, Winarto Eka; Aprilianto, Dwi (Jurnal Penelitian Pendidikan Islam, 2022)
The purpose of this study was to describe learning planning, implementation of learning, and evaluation of Islamic religious education learning at SLB Negeri Gunungsari Boonegoro during the COVID-19 pandemic. This study used qualitative research apprtoaches with descriptive methods. The data collection methods are interviews and documentation. The data were collected by interviews and documentation. The data analysis technique used an interactive analysis model which included four components, namely data collection, data reduction, data presentation and drawing conclusions. This study found that (1) planning lessons for blind and mentally retarded students, analyzing effective days, compiling syllabus, planning learning programs and conducting assessments, teachers are more concerned with the availability of visual aids as media in the learning process; (2) the implementation of learning for blind and mentally retarded students emphasizes direct application or practice of reading iqra' for mentally retarded and procedures for carrying out prayers for the blind with concrete objects or real objects; (3) evaluation of learning outcomes of Islamic religious education for blind and mentally retarded children evaluation is more measured from the results of direct observation and practice.